Penerapan Metode Linier Programming dalam Penentuan Kombinasi Produk - Edi Purwanto (Department Industrial Engineering, University of Muhammadiyah Malang, 2008)
This Research was conducted in PT X Tbk, Pandaan as a mean to look for combination amount of optimal product. PT X Tbk in the field of plastic production, goods the produced bottle by is assorted of size measure and colour. As for bottle the taken Image of Chamomile and of Nivea, while colour of Image bottle of Chamomile is green and its size measure is 120 ml and 250 ml. For the bottle of white Nivea chromatic and its size measure is 100 ml and 200 ml. From various produced bottle type cause incidence of a problem of that is problem of determination of less precise production volume. This matter is known from often happened product insuffiency or excess causing the loss of opportunity of request so that obtained advantage less optimal. In research to determine optimal product combination with Linear Programming method through two phase, that is first request of forecasting by using method of time series constructively Minitab software among others Moving Average, Single Exponential Smoothing, Double Exponential Smoothing, Winter’S and of Trend Linear, and second stage to conduct calculation of Linear Programming model constructively QS. From result of calculation by using QS hence got optimal solution of product combination between Image bottle of Chamomile 120 ml Green, Image of Chamomile 250 ml Green, Nivea 100 ml Slimdes RW White, and Nivea 200 ml Slimdes RW White which must produce. As for obtained advantage from after applying of Linear Programming method representing result of calculation during 12 period is equal to Rp421,918,752, while obtained advantage before conducted by Linear Programming is Rp410,250,750, so that happened the make-up of advantage equal to 2.84% that is Rp11,668,002.